How Can Social Capital Become a Facilitator of Inclusion? - Anett Hrabéczy; Tímea Ceglédi; Katinka Bacskai; Gabriella Pusztai (MDPI AG, 2023)
Students with special educational needs are a diverse group. Promoting their learning success is particularly challenging, even in practice for inclusive schools. At the same time, parents are often left alone with diagnosis and treatment. Therefore, the focus of our study was on the families of successful students with special educational needs and the networks around their families. Our research question is: What are the differences in social capital between parents of successful students with and without learning, behavioural and emotional disorders, and difficulties (SEN B)? We analysed the survey Value-Creating Education 2020 (n = 1156). Parents of 10-year-old children were asked whether their child needs special education services because of difficulties in learning. We used separate ordinal regression models to examine predictors of academic achievement in the two subsamples of parents of students with and without special educational needs (SEN B). Our results showed that factors supporting success differed between the two groups. Family background and involvement of professional helpers (teachers, psychologists, special education teachers) in child-raising were not among the predictors of academic success for students who need special education services because of learning problems, but the availability of an extensive network of the family had a positive significant effect.